2014
DOI: 10.1037/a0037098
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of cognitive behavioral social skills training for schizophrenia: Improvement in functioning and experiential negative symptoms.

Abstract: Objective Identifying treatments to improve functioning and reduce negative symptoms in consumers with schizophrenia is of high public health significance. Method In this randomized clinical trial, participants with schizophrenia or schizoaffective disorder (N=149) were randomly assigned to cognitive behavioral social skills training (CBSST) or an active goal-focused supportive contact (GFSC) control condition. CBSST combined cognitive behavior therapy with social skills training and problem solving training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 55 publications
(98 reference statements)
4
101
1
6
Order By: Relevance
“…149) untersuchten Granholm et al [2013Granholm et al [ , 2014 eine Erweiterung des SST um Elemente der kognitiven Therapie und fanden jeweils einen signifikanten Rückgang der motivationalen, nicht jedoch der expressiven Negativsymptomatik. In der größeren der beiden Studien [Granholm et al, 2014] waren diese Symptomverbesserungen auch im Vergleich zur aktiven Kontrollbedingung (supportive Gruppentherapie) signifikant (ES = -0,72), wobei die Unterschiede erst zum Katamnesezeitpunkt 12 Monate nach Therapieende deutlich wurden. Eine Kombination von SST und KR zeigte ebenfalls keinen Effekt auf die expressive Negativsymptomatik [Galderisi et al, 2010], wobei die Ergebnisse zur motivationalen Negativsymptomatik nicht berichtet wurden.…”
Section: Soziales Kompetenztrainingunclassified
“…149) untersuchten Granholm et al [2013Granholm et al [ , 2014 eine Erweiterung des SST um Elemente der kognitiven Therapie und fanden jeweils einen signifikanten Rückgang der motivationalen, nicht jedoch der expressiven Negativsymptomatik. In der größeren der beiden Studien [Granholm et al, 2014] waren diese Symptomverbesserungen auch im Vergleich zur aktiven Kontrollbedingung (supportive Gruppentherapie) signifikant (ES = -0,72), wobei die Unterschiede erst zum Katamnesezeitpunkt 12 Monate nach Therapieende deutlich wurden. Eine Kombination von SST und KR zeigte ebenfalls keinen Effekt auf die expressive Negativsymptomatik [Galderisi et al, 2010], wobei die Ergebnisse zur motivationalen Negativsymptomatik nicht berichtet wurden.…”
Section: Soziales Kompetenztrainingunclassified
“…Longitudinal investigations of defeatist performance beliefs in individuals with schizophrenia have largely been conducted in the context of cognitive therapy clinical trials, which have found some support for an association between a reduction in defeatist performance beliefs and improved negative symptoms and functioning over time (Granholm et al, 2013;Granholm et al, 2014). However, the longitudinal relationship between negative symptoms and other types of dysfunctional beliefs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent psychosocial treatments have shown efficacy in improving a subset of negative symptoms (Grant et al, 2012;Granholm et al, 2014;Grant et al, 2014), negative symptoms can often persist despite psychosocial treatments and antipsychotic medication (Tandon et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Debido al escaso impacto de estos programas, diversos autores han propuesto algunas mejoras para incrementar su eficacia. Por ejemplo, Granholm et al (2014;2007) han obtenido resultados prometedores combinando el EHS con la terapia cognitivo-conductual (TCC) en adultos con esquizofrenia.…”
Section: Modelos Actuales De Entrenamiento En Habilidades Sociales Paunclassified